Mind Map : Learning Model to Improve Creative Thinking Ability - Wida Wulandari (Perspektif Pendidikan dan Keguruan, 2023)
Twenty-first-century skills are essential for students. The purpose of this study is to determine the influence of the use of mind-mapping learning models in improving students' creative thinking, besides that it also aims to find out the differences in the average creative thinking ability of students who use the mind-mapping learning model. The research data that has been collected is processed using SPSS software version 24. The research hypothesis was tested using the Wilcoxon test and the Mann-Whitney U test. Based on the study's results, the application of the mind-mapping learning model impacts students' creative thinking ability. and the use of traditional learning models has no effect on students' abilities. Creative thinking of students. The average creative thinking ability of students who use the mind-mapping learning model is higher than that of traditional learning models.